Stability of Backfilled Cross-panel Entries During Longwall Miningq - Brad Seymour; Doug Tesarik; Mark Larson; Joe Shoemaker (The National Institute for Occupational Safety and Health (NIOSH))
In cooperation with Cyprus Twentymile Coal Co., researchers from the National Institute for Occupational Safety and Health (NIOSH), Spokane Research Laboratory, conducted a study at the Foidel Creek Mine, an underground coal mine near Oak Creek, CO, to evaluate the stability of underground working conditions as a longwall advanced through a series of backfilled cross-panel entries. Instruments installed in the cross-panel entry pillars, backfill, longwall panel, and adjacent headgate entry were continuously monitored by a computerized data acquisition system as the longwall approached and advanced through the backfilled section of the panel. Data collected from these instruments were analyzed to determine the magnitude and direction of the secondary principal stress changes ahead of the longwall face, deformation and closure of the headgate entry, and stability of the cross-panel entry pillars and backfill. A three-dimensional, boundary element model was calibrated to accurately predict mining-induced stress changes and the distance they occurred ahead of the longwall face. As the longwall advanced through the backfilled entries, most of the mining-induced load was supported by the cross-panel entry pillars. The backfill provided stability for the roof and floor of the in-panel entries and also confined the entry pillars significantly improving their load-carrying capacity. Comprehensive information derived from backfill material property tests, instrument data, underground observations, and numeric modeling results document the safety and stability of the 8-Right mine through and should provide beneficial case study information for other longwall backfilling applications in the future.